The Labours of Leisure: Work and Workers at the Annual Encampments of the American Canoe Association, 1880–1910 - Dunkin, Jessica (Labour / Le Travail, 2014)
The late 19th century witnessed an explosion of interest in canoeing as sport, recreation, and leisure in Canada, the United States, and Britain. One of the enduring legacies of the “canoe boom” was the American Canoe Association (ACA), a transnational organization established in 1880 to “unite all amateur canoeists for the purpose of pleasure, health, or exploration.” Annual meetings were central to realizing this mission. For two weeks in August, hundreds of enthusiasts from Canada and the United States came together to camp out, socialize, and race canoes. The encampments would not have occurred – or at the very least they would have looked drastically different – without the carpenters, cooks, servers, performers, and general labourers the organization hired to do the heavy work of construction, maintenance, and service. In spite of their importance, these workers exist, at best, on the margins of the official accounts of the meets; in most cases, they are altogether ignored. Recovery of this labouring past is difficult, and admittedly fragmentary. However, it is critical to the history of labour and of sport.